METODE CREATIVE PROBLEM SOLVING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI MAKNA SILA-SILA PANCASILA - Dwi Adelia Fandia Putri; Reza Rachmadtullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research stems from the fact that students' critical thinking skills are still relatively low. This condition is evident during learning activities, where many students struggle to think critically. The objective of this study is to assess how effectively the Creative Problem Solving (CPS) method enhances students' ability to analyze and interpret the meaning of each Pancasila precept. The research was conducted using a quasi-experimental approach with a Post-test Only design. The findings indicate that, based on the normality test, the data from the experimental group did not follow a normal distribution, while the control group's data did. Additionally, the homogeneity test revealed that the variance between the two groups was not uniform. Given these results from the classical assumption test—where one group had non-normally distributed data and the other showed unequal variance—the study proceeded with the Mann-Whitney test. The analysis using this test produced a significance level of 0.000, which is below the 0.05 threshold. Consequently, the findings confirm that the CPS method plays a role in enhancing students' critical thinking skills.